Estimated Cost And Time For Completion Of The Bali GX Office And Co Working Project Using The Earned Value Method - Rohim, Abd.; Witjaksana, Budi; Teki Tjendani, Hanie (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
The GX Office & Co Working Bali construction project faced significant delays in the 27th week with a deviation of -4.31%, which could result in increased costs and delays in completion. So, an effective solution is needed to overcome project delays and ensure that the project is completed on time and within budget. This research aims to examine the application of the Earned Value Method (EVM) in evaluating the performance of the GX Office & Co Working Bali project by calculating the Estimated Temporary Schedule (ETS), Estimated All Schedule (EAS), Estimate Temporary Cost (ETC) and Estimate All Completion (EAC). The research uses descriptive quantitative methods by collecting data from weekly project progress reports, actual costs, and planned values. Data analysis was carried out by calculating Planned Value (PV), Earned Value (EV), Actual Cost (AC), Cost Performance Index (CPI), Schedule Performance Index (SPI), ETS, EAS, ETC, and EAC. The research results show an ETS value of 114 days with an EAS of 303 days. So, there is an additional time of 9 days from the planned schedule. ETC results amounted to IDR 3,723,631,710.12, with EAC amounting to IDR 7,699,818,710.12. So, the cost of completing the project is lower than planned, with a difference of IDR 2,545,727,760.88. The results of this research contribute to the project management literature by showing the effectiveness of EVM in identifying deviations and the basis for making strategic policies needed so that projects can be completed on time according to plan.